Measuring gross beryllium erosion with visible cameras in JET. (1st December 2022) - de la Cal, E.; Losada, U.; Balboa, I.; Borodin, D.; Borodkina, I.; Brezinsek, S.; Carvalho, P.; Dittmar, T.; Douai, D.; Huber, A.; Huber, V.; Karhunen, J.; et al.
Abstract: Two visible cameras with the same wide-angle view have been used to study the gross beryllium (Be) erosion in JET. An absolutely calibrated spectroscopy system employed in the past for the same object was used to quantitatively infer the camera photon fluxes and also to validate the results. To extract the effective sputtering yield, a simplified method is applied from the quotient of the measured radiances of the D α and the Be II line at 527 nm. The obtained results are in reasonably good agreement with those already published. The main benefit of using cameras is that the global view of the plasma–wall interaction surfaces of the whole vessel is monitored, and the different sources and their wetted areas can be identified and quantified. In addition, the measurement of the particle flux distributions can be used for the validation of three-dimensional erosion-transport codes.